2021
DOI: 10.1038/s41419-021-03495-0
|View full text |Cite
|
Sign up to set email alerts
|

CircRNAs: a new target for the diagnosis and treatment of digestive system neoplasms

Abstract: A circRNA is a type of endogenous noncoding RNA that consists of a closed circular RNA molecule formed by reverse splicing; these RNAs are widely distributed in a variety of biological cells. In contrast to linear RNAs, circRNAs have no 5′ cap or 3′ poly(A) tail. They have a stable structure, a high degree of conservation, and high stability, and they are richly and specifically expressed in certain tissues and developmental stages. CircRNAs play a very important role in the occurrence and progression of malig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 91 publications
0
33
0
Order By: Relevance
“…The proliferation and migration of endometrial tissue outside of the uterus is a vital character of endometriosis; whereas the exact pathological progression remains largely unknown [20]. CircRNAs has been recognized as important molecules involving in various biological processes and its abnormality may contribute to many diseases [3]. Studies have showed abnormal expression of circRNAs in endometriosis and indicated their diagnosis value in in discerning diseases at earlier time [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proliferation and migration of endometrial tissue outside of the uterus is a vital character of endometriosis; whereas the exact pathological progression remains largely unknown [20]. CircRNAs has been recognized as important molecules involving in various biological processes and its abnormality may contribute to many diseases [3]. Studies have showed abnormal expression of circRNAs in endometriosis and indicated their diagnosis value in in discerning diseases at earlier time [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Circular RNAs (circRNAs) are a class of endogenous RNAs with closed loop structure which ascertained the more stability than linear RNAs. With high abundance and speci c expression in different tissues or developmental stages, circRNAs have been revealed to participate in the regulation of biological and pathological processes such as cell proliferation, apoptosis, invasion, angiogenesis and epithelialmesenchymal transformation, by acting as microRNA (miRNA) sponges [3,4]. Evidences have demonstrated aberrant circRNA expression in endometriosis [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Circular RNAs (circRNAs) are a class of endogenous RNAs with a closed loop structure that makes them more stable than linear RNAs. circRNAs are highly abundant and specifically expressed in different tissues and developmental stages and have been found to participate in the regulation of biological and pathological processes such as cell proliferation, apoptosis, invasion, angiogenesis, and the epithelial-mesenchymal transition (EMT), by acting as microRNA (miRNA) sponges [3][4][5]. Previous studies have found aberrant circRNA expression in endometriosis [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Circular RNAs (circRNAs) are a type of endogenous non-coding RNA that do not have a 5'-cap or a 3'-polyA tail and are implicated in a variety of biological functions [4][5]. Recently, RNA-sequences revealed that circRNAs are involved in diagnosis, prognosis, development, and drug resistance in tumors.…”
Section: Introductionmentioning
confidence: 99%